Military borders, political frontiers: settling the Portuguese urban space in North Africa - Correia, Jorge (2020)
Unlike Mazagão, which represents the long-lasting Portuguese new settlement in North Africa (1514-1769), the Portuguese urban experience mainly opted for the occupation of existing Muslim cities in the region. In fact, during the fifteenth and sixteenth centuries, five coastal cities were seized and undertook an occupational praxis that implied a surface downsizing by new curtain walls, called atalho, and a revision of the street layout. In a territory where fortified perimeters often acted as borders, the former Islamic matrix implied not only a re-dimensioning of the urban space, but also a will of erasing the previously built footprint. Military architecture and urban morphology were to become coherent with the European culture, at a time when urban concepts and practices were being renewed through the hygienist and rationalist spirit inherent to the winds of early modernity. Historical cartography and recent fieldwork allow retrospective keys to the reading of these legacies.